Assessing Small Bowel Stricturing and Morphology in Crohn's Disease Using Semi-automated Image Analysis. Issue 5 (29th August 2019) - Stidham, Ryan W; Enchakalody, Binu; Waljee, Akbar K; Higgins, Peter D R; Wang, Stewart C; Su, Grace L; Wasnik, Ashish P; Al-Hawary, Mahmoud
Abstract: Background: Evaluating structural damage using imaging is essential for the evaluation of small intestinal Crohn's disease (CD), but it is limited by potential interobserver variation. We compared the agreement of enterography-based bowel damage measurements collected by experienced radiologists and a semi-automated image analysis system. Methods: Patients with small bowel CD undergoing a CT-enterography (CTE) between 2011 and 2017 in a tertiary care setting were retrospectively reviewed. CT-enterography studies were reviewed by 2 experienced radiologists and separately underwent automated computer image analysis using bowel measurement software. Measurements included maximum bowel wall thickness (BWT-max), maximum bowel dilation (DIL-max), minimum lumen diameter (LUM-min), and the presence of a stricture. Measurement correlation coefficients and paired t tests were used to compare individual operator measurements. Multivariate regression was used to model identification of strictures using semi-automated measures. Results: In 138 studies, the correlation between radiologists and semi-automated measures were similar for BWT-max ( r = 0.724, 0.702), DIL-max ( r = 0.812, 0.748), and LUM-min ( r = 0.428, 0.381), respectively. Mean absolute measurement difference between semi-automated and radiologist measures were no different from the mean difference between paired radiologists for BWT-max (1.26 mm vs 1.12 mm, P = 0.857), DIL-max (2.78 mm vs 2.67 mm, P = 0.557), and LUM-min (0.54 mm vs 0.41 mm, P = 0.596). Finally, models of radiologist-defined intestinal strictures using automatically acquired measurements had an accuracy of 87.6%. Conclusion: Structural bowel damage measurements collected by semi-automated approaches are comparable to those of experienced radiologists. Radiomic measures of CD will become an important new data source powering clinical decision-making, patient-phenotyping, and assisting radiologists in reporting objective measures of disease status. Abstract : Measurements of bowel damage using automated computer imaging analysis have similar agreement compared with experienced abdominal radiologists. Automated imaging analysis systems can also identify qualitative features with very good accuracy, providing quantitative descriptions of phenotype, damage, and activity in patients with Crohn's disease.